2008
DOI: 10.1016/j.bmcl.2008.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Epiboxidine and novel-related analogues: A convenient synthetic approach and estimation of their affinity at neuronal nicotinic acetylcholine receptor subtypes

Abstract: a b s t r a c tRacemic exo-epiboxidine 3, endo-epiboxidine 6, and the two unsaturated epiboxidine-related derivatives 7 and 8 were efficiently prepared taking advantage of a palladium-catalyzed Stille coupling as the key step in the reaction sequence. The target compounds were assayed for their binding affinity at neuronal a4b2 and a7 nicotinic acetylcholine receptors. Epiboxidine 3 behaved as a high affinity a4b2 ligand (K i = 0.4 nM) and, interestingly, evidenced a relevant affinity also for the a7 subtype (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…8,10 Phosphoric acid, formic acid, acetic acid, boric acid, 3-(cyclohexylamino)-1-propanesulfonic acid (CAPS), sodium hydroxide, CO2 free potassium hydroxide, potassium chloride, potassium hydrogen phthalate (KHP), hydrochloric acid (0.5 M), acetone and methanol were purchased from Sigma-Aldrich. All reagents used were of analytical grade and all reagents and buffers were prepared with water obtained from a Milli-Q water purification system (Millipore).…”
Section: Chemicalsmentioning
confidence: 99%
See 3 more Smart Citations
“…8,10 Phosphoric acid, formic acid, acetic acid, boric acid, 3-(cyclohexylamino)-1-propanesulfonic acid (CAPS), sodium hydroxide, CO2 free potassium hydroxide, potassium chloride, potassium hydrogen phthalate (KHP), hydrochloric acid (0.5 M), acetone and methanol were purchased from Sigma-Aldrich. All reagents used were of analytical grade and all reagents and buffers were prepared with water obtained from a Milli-Q water purification system (Millipore).…”
Section: Chemicalsmentioning
confidence: 99%
“…[2][3][4][5] Efforts in this research area have mainly focused on the discovery and development of agonists selectively interacting with α4β2 and α7 subtypes, 6 which are the two main populations of nicotinic receptors in the human brain and thus the most relevant biological targets for potential therapeutic applications. In this frame, epibatidine 1, a highly toxic alkaloid identified in the skin of the Ecuadorian frog Epipedobates tricolor, 7 epiboxidine 2, 8 an epibatidine analogue in which the chloropyridinyl ring has been replaced by the 3-methylisoxazolyl moiety, and ARR1779 3 9 are endowed with high affinity for both the α4β2 and α7 nAChR subtype (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, for DM and LM there was no significant difference in the ΔS° values, while the ΔH° value for the DMnAChR interaction was significantly lower than respective value for LM-nAChR interaction showing that the enantioselectivity of 3 4 nAChR is mostly enthalpy-based (Jozwiak et al, 2003).The results of those studies demonstrated that non-linear chromatography approach of investigations of immobilized nAChRs can be useful in characterizing ligand-receptor binding interactions and predicting of properties of drugs and drug candidates. Additional NLC studies with this system were used to construct QSAR models of non-competitive inhibitors of the nAChR (Jozwiak et al, 2004), to develop a molecular model of these interactions (Jozwiak et al, 2004) and to predict IC 50 values ] -bungarotoxin as marker radioligands specific for 3 4 and 7 nAChRs subtypes respectively were applied to determine K i values and check subtype selectivity of newly synthesized derivatives of epiboxidine, synthetic epibatidine-related compounds (Rizzi et al, 2008).…”
mentioning
confidence: 99%